Resiliensi dan Kematangan Karier terhadap Quarter-Life Crisis pada Mahasiswa Fresh Graduate UIN Sumatera Utara - Rianti, Irna; Suhairi, Suhairi; Aslami, Nuri (Universitas Proklamasi 45, 2025)
This study examines whether resilience and career maturity explain variance in quarter-life crisis (QLC) among fresh graduates of the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra. Using a quantitative correlational design with purposive sampling (2023–2024 graduates), validated Likert-type scales captured resilience (CD-RISC-based), career maturity (planning, exploration, occupational information, decision-making), and QLC indicators. After meeting classical assumptions, multiple linear regression showed a jointly significant model (R² = .443; Adjusted R² = .432). Partially, higher resilience related to lower QLC, and career maturity had a significant negative effect on QLC, supporting a dual-path account in which psychological hardiness and vocational clarity jointly mitigate early-career identity strain. Practical implications recommend an integrated career-readiness + resilience package (career clinics, decision-making and job-search training, structured internships/projects, personal finance education, and digital well-being). Limitations include cross-sectional design, self-report measures, and a 10% margin of error; future work should adopt longitudinal/SEM approaches to test mediating or moderating mechanisms (e.g., career efficacy, peer support, family economy, functional religiosity).